The Concepts of al-Fana’ and al-Baqa’ in Hasan Hanafi’s Thought and Their Implications in Contemporary Life: Konsep al-Fana’ dan al-Baqa’ dalam Pemikiran Hasan Hanafi dan Implikasinya dalam Kehidupan Kontemporari - Wahyudi, Andi; Syahrul, Muzakkir; Adenan (Jurnal Usuluddin, 2025)
This study explores Hasan Hanafi’s reconstruction of ‘Ulum al-Tasawwuf through the paradigm of ‘Min al-Fana’ ila al-Baqa’’ and examines its implications for contemporary life. Hasan Hanafi criticizes forms of tasawwuf that excessively emphasize inward spirituality while neglecting practical and social engagement, arguing that such tendencies hinder the productivity and creativity of the Muslim community. In response, he proposes a transformative model of tasawwuf that shifts from passive and ritualistic spirituality toward an active, dynamic, and socially responsible discipline. Central to this reconstruction is the concept of objective consciousness (wa‘y maudhu‘iy), which reorients faith from a submissive and static condition into a form of revolutionary morality (akhlaq al-thawriy). This moral framework is grounded in the paradigm of al-baqa’ on earth, prioritizing the actualization of human khilafah (vicegerency) over the mere pursuit of individual sainthood (wilayah). Hasan Hanafi argues that true sainthood emerges only through the successful realization of humanity’s role as God’s vicegerent on earth. Furthermore, this study highlights Hasan Hanafi’s insistence on orienting tasawwuf as an individual spiritual experience (tajribah fardiyah) rather than a collective or institutionalized practice, which he considers potentially harmful when transformed into mass movements. Methodologically, this research employs qualitative library research with a descriptive-analytical approach, focusing primarily on Hasan Hanafi’s Min al-Fana’ ila al-Baqa’ as the main source. The findings demonstrate that Hasan Hanafi’s project aims to revitalize tasawwuf as a productive, humanistic, and civilization-oriented discipline capable of contributing meaningfully to modern social life, education, and cultural development.